Dualism In The Settlement of Jinayat Cases, Which Includes General Crimes in Sabang City - Manihuruk, Erick Jeremi; Mulyadi, Mahmud; Trisna, Wessy; Andriati, Syarifah Lisa (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
Implementing jinayat law enforcement in Sabang of Aceh Province experiences a dualism of settlement, which causes legal uncertainty. This can be observed in practice where the Sabang District Court instead adjudicates cases that should be under the jurisdiction of the Sabang Sharia Court. This article elaborates on the dualism in the settlement that occurs and identifies the causes of the dualism in the settlement of criminal cases using Soerjono Soekanto's law enforcement factor theory. Based on that, efforts were found that could be made to overcome this dualism. The analysis results indicate that the dualism of settlement can be observed through 6 (six) cases that should be under the jurisdiction of the Sabang Sharia Court but were adjudicated by the Sabang District Court, the majority of which are minor-related cases. There are cases where the same defendant is tried in close succession in both judicial institutions for similar acts with different victims. It happens due to various factors, such as the legal factor: inadequate provisions regarding minors at Qanun Jinayat. Law enforcer factor: other views on minor-related cases and a lack of precision in implementing existing law. Facilitating factor: unavailability of detention rooms at Sabang Sharia Court and budget for executions. Society factors: public lack of legal knowledge. Based on the results of this identification, efforts can be made to include professional law enforcement, harmonization of judicial authority through internal agency regulations, and evaluation of moral offenses in the Qanun Jinayat.